TINJAUAN KUALITAS HASIL WlRAUSAHA BARU PRODUKSI BAHAN BANGUNAN (BATAKO) ANAK-ANAK PANTI ASUHAN YATIM PIATU BASA MOYUDAN. SLEMAN. YOGYAKARTA - Darmono, Darmono (Universitas Negeri Yogyakarta, 2003)
Skill education to support life skill needs to be encouraged for each educationlevel including non-formal education. This is as done by the children in the BASA Orphanage, Moyudan, Sleman, Yogyakarta. that has pioneered new entrepreneur in the field of building material production especially concrete block (batako). The problems are: (1) How far is the produced concrete block quality viewed on physical and mechanical characteristics?, and (2) Which category is the produced concrete block viewed on its shear stress?The research was conducted by field survey and laboratory test especially toobserve the shear stress of the produced concrete block. The research samples were defined as recommended by the SII Number 0284-80. 10 test materials for each test types. The physical characteristic observation on the produced concrete blocks includes the tests of: (1) Water absorption, (2) Water content, (3) Specific weight, (4) Outside appearance, and (5) Volume weight. The observation on mechanicalcharacteristic is focused on the shear stress of the produced concrete blocks. All of the research activities were conducted in shaping location and the Building Materials and Testing Laboratory. The data collecting technique applies method of noting all the field and laboratory test results. The data analysis technique was conducted qualitatively by presenting the mean.The research shows that the produced concrete blocks with the ratio of 1 PC :12 Sand. have the mean values of: (1) Water absorption of 12.97%; (2) Water contentof 9.07%; (3) Specific weight of 2.11 gr/crrr' ; and (4) Outside appearances: right angled edges. not defect. and the edge decay of 60% good. Whilst viewed on the mechanical characteristic especially the shear stress. It shows the mean value of20.155 kg/cnr', classified as Al quality.Key words: new entrepreneur, building materials, and orphanage